Socio-Environmental Determinants and Human Health Exposures in Arid and Semi-Arid Zones of Iran—Narrative Review. (April 2022) - Kalankesh, Laleh R.; Rodriguez-Couto, Susana; Alami, Ali; Khosravan, Shahla; Meshki, Mehdi; Ahmadov, Elshan; Mohammadpour, Ali; Bahri, Narjes
Lifestyle is different in arid and semi-arid zones. However, where people are born and live have a lasting influence on their social and environmental exposure. This review focuses on the, various dimensions of environmental health imbalance inequality especially in significant environmental sources such as (ie, air, water, soil) among provinces that creates a big health gap in the center, East and the Southeast of Iran. Thus, the population of the arid and semi-arid zones of Iran is facing respiratory, cardiovascular, cancer and infection diseases linked to environmental problems such as chemical and microbial pollution due to air pollution and unsafe water sources, respectively. The prevalence of certain types of cancer such as skin, stomach, bladder, prostate and colorectal cancer together with some respiratory and cardiovascular diseases in arid and semiarid zones such as Kerman, Yazd, etc., has been reported in comparison with other provinces frequently. These impacts have effects on multiple levels of health security in those zones. Based on these concerns, we propose key questions that should guide research in the context of the socio environmental science to support science-based management actions in Iran and other similar semi-arid areas worldwide.